ANALISIS PELUANG WIRAUSAHA MAHASISWA POLITEKNIK NEGERI MEDAN DI ERA EKONOMI DIGITAL - Anggita Refany Pramudya; Inayah Ranitya; Trinita Siringo Ringo; Vita Olivia Silalahi (CV. Denasya Smart Publisher, 2026)
The rapid development of technology in Indonesia has brought significant changes to various sectors, particularly the economic sector. Digitalization has not only changed the patterns of interaction and community activities but also opened up new opportunities in the business world, including for students at the Medan State Polytechnic. As part of the younger generation, students are required to be able to adapt to technological developments, utilize digital innovations, and develop relevant skills to remain competitive. Digital entrepreneurship opportunities such as e-commerce, mobile applications, and online-based services provide space for students to build and develop businesses. However, various challenges such as high competition, the demand for innovation, and limited knowledge about digital business management remain major obstacles. This study aims to identify entrepreneurial opportunities for Medan State Polytechnic students in the digital economy era, analyze the factors that influence their interest and ability in digital-based entrepreneurship, and examine the obstacles faced in starting a digital business. The results of this study are expected to provide a comprehensive understanding of the opportunities and obstacles in student entrepreneurship, and encourage the creation of a young generation that is not only job-seeking but also able to create jobs through the use of digital technology.